Islamic Digital Wisdom: Formulation of Social Media Ethics Based on Hadith to Address the Digital Moral Crisis - Saifuddin, Fathan Ghifari; Musyafiq, Ahmad; Rochmawati, Nikmah (Al-Bukhari : Jurnal Ilmu Hadis, 2025)
The issue of moral and ethical degradation in the use of social media in the digital era has increasingly intensified, as evidenced by the widespread circulation of hoaxes, hate speech, and other forms of destructive communication behavior. This study aims to analyze the principles of wise social media engagement based on the teachings of the hadith of the Prophet Muhammad saw, as a foundation for digital ethics from an Islamic perspective. The research employs a qualitative approach using thematic (maudhu‘i) analysis of hadiths related to communication ethics and social behavior, complemented by content analysis to contextualize the messages of the hadith within contemporary digital realities. The findings identify four operational hadith-based digital ethical principles: (1) information integrity, manifested in the obligation of tabayyun to counter hoaxes and misinformation; (2) control of digital expression, emphasizing the prohibition of destructive anger and hate speech; (3) public communication etiquette, encompassing guidance to speak kindly, avoid ghibah, and uphold mutual dignity; and (4) social responsibility, namely the obligation to disseminate benefit and avoid content that causes social harm. The contribution of this study lies in the formulation of the “Islamic Digital Wisdom” model as a comprehensive digital ethics framework that integrates hadith values into the dynamics of modern cyberspace as a moral solution for social media users.